Selective brain cooling: Let us have a moment of science. Issue 1 (January 2019) - Almekhlafi, Mohammed A; Colbourne, Fred; Al Sultan, Abdulaziz S; Goyal, Mayank; Demchuk, Andrew M
Selective brain cooling is a promising advent for reducing final infarct volume and improving outcomes in ischemic stroke victims. Despite the robust body of evidence from animal studies, evidence supporting the use of selective hypothermia in stroke patients is lacking. A recent study provided promising results on the safety and possible efficacy of selective brain hypothermia via intraarterial infusion of cooled saline. Better understanding of the patients' population that may attain benefit from this approach will be informative. Details of infarct progression using perfusion imaging will also help understand the mechanism of effect of selective hypothermia to inform future trials.